2017
DOI: 10.18632/oncotarget.17064
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of drug-response heterogeneity rapidly generated from a single cancer cell

Abstract: One cancer cell line is believed to be composed of numerous clones with different drug sensitivity. We sought to investigate the difference of drug-response pattern in clones from a cell line or from a single cell. We showed that 22 clones derived from 4T1 cells were drastically different from each other with respect to drug-response pattern against 11 anticancer drugs and expression profile of 19 genes associated with drug resistance or sensitivity. Similar results were obtained using daughter clones derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…6). Cells within a tumor and cancer line populations are heterogeneous, partially explaining why an entire cell population is not killed by Yoda1-TRAIL treatment 33,34 . To account for this heterogeneity, a random population of cells was generated by creating a random-normal distribution of cytosolic Bcl-2, as this altered the necessity of calcium (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6). Cells within a tumor and cancer line populations are heterogeneous, partially explaining why an entire cell population is not killed by Yoda1-TRAIL treatment 33,34 . To account for this heterogeneity, a random population of cells was generated by creating a random-normal distribution of cytosolic Bcl-2, as this altered the necessity of calcium (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similar arguments can be made as lower complex 4 concentrations take longer to affect a heterogeneous cell population. 4T1-luc cells are known to be highly heterogeneous regarding genetic profiles [241] and effects of chemotherapeutic drugs [242]. Thus, it is not unexpected that 4T1-luc cells have different levels of sensitivity to complex 4 with higher concentration affecting some cells rapidly (2 h) and affecting a more resistant population later (6 h).…”
Section: Modulation Of the Mitochondrial Transmembrane Potential (δψ mentioning
confidence: 99%
“…Heterogeneity of cellular drug response is a commonly reported phenomenon in cancer treatment, yet mechanisms underlying this are not well understood. 29 Analysis of cell volumes showed the mean volume of treated and untreated cells to be comparable for doxorubicin reflecting the fact that this treatment can induce G1, S or G2 cell cycle arrest. 30 However, for docetaxel treated cells, we found that clusters spanned a range of mean cell volumes beyond those of the untreated set for both cell lines.…”
Section: Discussionmentioning
confidence: 99%